2020
DOI: 10.1007/s11669-020-00844-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alloy Composition and Solid-State Diffusion Kinetics on Powder Bed Fusion Cracking Susceptibility

Abstract: Laser powder bed fusion (LPBF) has demonstrated its unique ability to produce customized, complex engineering components. However, processing of many commercial Al-alloys by LPBF remains challenging due to the formation of solidification cracking, although they are labelled castable or weldable. In order to elucidate this divergence, solidification cracking susceptibility from the steepness of the solidification curves, specifically |dT/df S 1/2 |, as the fraction solidified nears 1 towards complete solidifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The peak in SCS predicted by the Scheil-Gulliver and DICTRA models occurs at slightly higher Cu content than the experimentally observed peak reported by Campbell et al [24]. However, the characteristic lambda shape commonly observed in SCS measurements of binary aluminum alloys [8] matches reasonably well with the experimental data as shown in Figure 2b. It is also observed that increasing the cooling rate during solidification pushes the solidification reaction further from equilibrium which, reduces the solidus temperature, increases microsegregation, and leads to increased SCS.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The peak in SCS predicted by the Scheil-Gulliver and DICTRA models occurs at slightly higher Cu content than the experimentally observed peak reported by Campbell et al [24]. However, the characteristic lambda shape commonly observed in SCS measurements of binary aluminum alloys [8] matches reasonably well with the experimental data as shown in Figure 2b. It is also observed that increasing the cooling rate during solidification pushes the solidification reaction further from equilibrium which, reduces the solidus temperature, increases microsegregation, and leads to increased SCS.…”
Section: Discussionsupporting
confidence: 82%
“…Computational models with the flexibility to predict non-equilibrium solidification in multicomponent materials are limited, and new computational frameworks are desired to design the next generation of additively manufactured materials. CALPHAD-based ICME (CALPHAD: Calculation of Phase Diagrams, ICME: Integrated Computational Materials Engineering) [4,5] frameworks have shown the ability to model the effects of non-equilibrium solidification in both welding and additive manufacturing process [6][7][8][9]. However, these models typically fail to couple the thermodynamics and kinetics of materials with changes in processing parameters.…”
Section: Introductionmentioning
confidence: 99%
“…During the L-PBF process, the rapid cooling rates are typically high and range from 10 5 to 10 8 K/s, compared with conventional casting rates, which typically occur at much lower rates of 10 1 to 10 3 K/s [20][21][22]. The rapid heating and cooling process results in large thermal gradients that then control the resulting microstructure, grain size and shape, and grain orientation.…”
Section: Introductionmentioning
confidence: 99%
“…The amount of nonbond fine powder can be reduced by ball milling of 3 h and more. Ball milling is accompanied by plastic deformation of the base powder leading to variations from the original spherical shape.Hot cracks are a known phenomenon in additive manufacturing (AM), which were observed by various researchers for different alloys: nickel-based materials, [8,9] tungsten, [10] aluminum-based alloys, [11] and steels. [12] Hot cracks form during solidification as the residual melt is trapped between solidified grains/dendrites and the melt flow in the interdendritic space is hindered.…”
mentioning
confidence: 99%
“…Hot cracks are a known phenomenon in additive manufacturing (AM), which were observed by various researchers for different alloys: nickel-based materials, [8,9] tungsten, [10] aluminum-based alloys, [11] and steels. [12] Hot cracks form during solidification as the residual melt is trapped between solidified grains/dendrites and the melt flow in the interdendritic space is hindered.…”
mentioning
confidence: 99%